Some new species and new records of corticioid fungi (Basidiomycota) from the Brazilian Amazon - Gorjón, S. P.; Jesus, Maria Aparecida de (Phytotaxa, 2012)
As a result of the revision of some herbarium specimens deposited in INPA (Manaus, Brazil) and new collections from the Brazilian Amazon, we report on 35 noteworthy species that are new records to the Brazilian Amazon. Dendrothele nakasoneae, D. ornata, Gloeodontia halocystidiata, Gloiothele incrustata, G. larssonii, and Peniophora wallacei are described as new. Comments and illustrations are given for most of the species. © 2012 Magnolia Press.